Interaction between H2O, N2, CO, NO, NO2 and N2O molecules and a defective WSe2 monolayer. Issue 38 (18th September 2017) - Ma, Dongwei; Ma, Benyuan; Lu, Zhiwen; He, Chaozheng; Tang, Yanan; Lu, Zhansheng; Yang, Zongxian
Abstract : The interaction of various gas molecules with a defective WSe2 monolayer is theoretically studied. The defective WSe2 monolayer exhibits enhanced sensing ability toward H2 O and N2 molecules. The doping of the WSe2 monolayer due to the interaction of CO, NO, NO2, and N2 O molecules with Se vacancies is discussed. Abstract : In this study, the interaction between gas molecules, including H2 O, N2, CO, NO, NO2 and N2 O, and a WSe2 monolayer containing an Se vacancy (denoted as VSe ) has been theoretically studied. Theoretical results show that H2 O and N2 molecules are highly prone to be physisorbed on the VSe surface. The presence of the Se vacancy can significantly enhance the sensing ability of the WSe2 monolayer toward H2 O and N2 molecules. In contrast, CO and NO molecules highly prefer to be molecularly chemisorbed on the VSe surface with the non-oxygen atom occupying the Se vacancy site. Furthermore, the exposed O atoms of the molecularly chemisorbed CO or NO can react with additional CO or NO molecules, to produce C-doped or N-doped WSe2 monolayers. The calculated energies suggest that the filling of the CO or NO molecule and the removal of the exposed O atom are both energetically and dynamically favorable. Electronic structure calculations show that the WSe2 monolayers are p-doped by the CO and NO molecules, as well as the C and N atoms. However, only the NO molecule and N atom doped WSe2 monolayers exhibit significantly improved electronic structures compared with VSe . The NO2 and N2 O molecules will dissociate directly to form an O-doped WSe2 monolayer, for which the defect levels due to the Se vacancy can be completely removed. The calculated energies suggest that although the dissociation processes for NO2 and N2 O molecules are highly exothermic, the N2 O dissociation may need to operate at an elevated temperature compared with room temperature, due to its large energy barrier of ∼1 eV.